Embryo/Fetus doses from 18F-fludeoxyglucose radiopharmaceutical in positron emission tomography/computed tomography - Nazenin Ipek Isikci; Mustafa Demir (Journal of Medical Physics, 2022)
Aim: The embryo/fetus may be accidentally exposed to ionizing radiation. The aim of this study is to calculate embryo/fetus doses in pregnant women who underwent F-18 fludeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) scan. Materials and Methods: Between June 2015 and June 2021, 15 pregnant women underwent F-18 FDG PET/CT applied to the Genetic Research Center (GETAM). The OLINDA/EXM package program was used for internal radiation dosimetry according to the Medical Internal Radiation Dose scheme. FetDose V4 computer software was used to compute the embryo/fetus absorbed dose from CT scan. Results: The amount of the injected F-18 FDG activity to patients varied between 333 and 555 MBq. The mean embryo/fetal dose from F-18 FDG was 7.2 ± 2.8 mGy. In addition, the CT component dose to the embryo/fetus dose ranged from 8.5 to 16 mGy with a mean of 12.14 ± 2.05. Conclusions: The embryo/fetus dose from F-18 FDG PET/CT was <15 mGy, however, questioning the women's childbearing prior to scintigraphy is the first-line strategy to avoid accidental radiation exposure and stochastic risks.